An empirical analysis on the shariah audit practices among takaful operators in Malaysia - Noor Aimi Mohamad Puad (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2020)
Shariah audit functions within Islamic financial institutions have been imposed by Bank Negara Malaysia (BNM) with the issuance of Shariah Governance Framework in 2011 (revised by Shariah Governance Policy 2019). During the early stage of the implementation, the Shariah audit approach focused on Shariah compliance aspects. After almost ten years, Shariah audit function becomes mandatory, and is expected to be properly established and able to achieve its primary objective. The function of Shariah audit should serve as an independent assessment of internal control for any Shariah non-compliance risk. Prior research revealed that insufficiency of specific guideline for Shariah audit has become the challenges for auditors to carry out a comprehensive Shariah audit procedure; rendering the present practice to heavily rely on the conventional audit framework. The study examines the present Shariah audit practice of Malaysian Takaful industry which consists of the process of Shariah audit, scope of Shariah audit and challenges in conducting Shariah audit. The study also assesses the perceptions of Shariah committee on the effectiveness of the current Shariah audit practices. The study adopts qualitative methods to meet the research purposes. Data were collected using document analysis and semi-structured interviews involving selected Shariah auditors, Shariah compliance officers and Shariah committee members in the Takaful industry. The findings provided an in-depth explanation on the process of Shariah audit, particularly the planning, executing, reporting and follow up as well as the scope developed by the auditors and challenges when conducting Shariah audit. The study proposes the a practical framework for the Shariah audit process to enhance the current practices. The first finding indicates that Takaful Operators presently adopts conventional framework and risk-based audit (RBIA) for their Shariah audit practices. The second finding showed that overall Shariah audit process and scope have achieved the required objective, yet, a specific standard framework is needed as a benchmark and reference point for Shariah auditors. Detailed explanation on the current Shariah audit process is expected to contribute to the provision of in-depth information for the Takaful Industry in particular, and other Islamic financial institutions in general to develop comprehensive strategy and robust internal control in order to manage and mitigate the occurrence of Shariah non-compliance risk. Finally, the perceptions of Shariah committee provide future directions of Shariah audit and further recommendations to enhance the current audit practices.